GAGASAN PENATAAN SISTEM LEGISLASI DALAM SISTEM PEMERINTAHAN PRESIDENSIAL DIKAITKAN DENGAN UPAYA MEWUJUDKAN SISTEM PARLEMEN DUA KAMAR YANG SAMA KUAT (STRONG BICAMERALISM) DI INDONESIA - Reynold M Panggabean; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The amendment to the 1945 Constitution of the Republic of Indonesia (the 1945 Constitution)has resulted in changes to the constitutional system including changes to Indonesia's legislation practicesand systems. The results of the amendments to the 1945 Constitution put the legislative function only inthe House of Representatives (DPR). As the second chamber of the parliament, the RegionalRepresentative Council (DPD) does not have a legislative function like the DPR. The absence of thelegislative function in the DPD made the DPD not optimal in fighting for regional interests at thenational level, and made the DPD limited to sub-ordination bodies rather than the DPR. Because theDPD does not have a legislative function as the main function of the representative room, the DPDcannot actually be said to be part of the Indonesian representative body. Because, the DPD in fact isweak and powerless in carrying out its representative functions as a regional representative body. Inaddition, the absence of a legislative function in the DPD gave rise to the risk of a situation of instabilityin the administration of the government carried out by the Government (president). Changes to the 1945Constitution place the practice of legislation carried out jointly by the Government (president) and theDPR. Because the DPD does not have a legislative function as the main function of the representativeroom, the DPD cannot actually be said to be part of the Indonesian representative body. Because, theDPD in fact is weak and powerless in carrying out its representative functions as a regionalrepresentative body. In addition, the absence of a legislative function in the DPD gave rise to the risk ofa situation of instability in the administration of the government carried out by the Government(president). Changes to the 1945 Constitution place the practice of legislation carried out jointly by theGovernment (president) and the DPR.This type of research can be classified in the type of normative juridical research, because inthis study the author uses legal literature material or mere secondary data as data in this study, the datasources used, primary legal materials, secondary legal materials and tertiary legal materials.From the results of the research and discussion of the problem there are two main things thatcan be concluded. First, the Indonesian legislative system after the amendment to the 1945 Constitutionhas not been able to realize a strong bicameralism in Indonesia. Post-change, the DPD does not have alegislative function like the DPR. Thus, the DPD as the second chamber of the representative body isnot in the same (relative) position as the DPR, in carrying out its duties and functions as the regionalrepresentative body. Second, in order to realize a strong parliamentary parliamentary system, thestructuring of the legislative system through formal amendments to the 1945 Constitution became animportant and urgent need to be realized. The arrangement of the legislative system was intended toeliminate the involvement of the president in the practice of joint discussion and approval of the draftlaw (RUU) with the DPR, while also providing the same legislative function to the DPD and DPR. Theauthor's suggestion, given that there have been so many shortcomings or weaknesses than theconstitutional system stipulated in the 1945 Constitution, the authors suggest that the formalamendments to the 1945 Constitution be realized immediately. It is expected that DPR members willopen themselves to help with the amount of quorum votes needed to implement the formal amendmentsto the 1945 Constitution.Keywords: Legislation System – DPD – Parliamentary System- Strong Bicameralism